Intralesional biologics for inflammatory dermatoses: A systematic review. Issue 2 (8th December 2021) - Seivright, Justine R.; Villa, Natalie M.; De, Devea R.; Hsiao, Jennifer L.; Shi, Vivian Y.
Abstract: Biologic medications are systemic therapeutic options for inflammatory dermatoses. Local forms of administration are less well‐studied. To provide a summary of intralesional (IL) administration of biologics for various non‐malignant inflammatory dermatologic conditions reported in the literature. A systematic review was performed in the PubMed and Embase databases from 2000 to 2020. Inclusion criteria included the local use of biologic medications for non‐malignant cutaneous conditions. Quality was assessed with the modified Oxford Centre for Evidence‐Based Medicine ratings. A total of 19 articles describing the use of 5 biologic medications in 9 dermatologic conditions were identified, comprising 172 patients. Conditions successfully treated with intralesional biologics included pemphigus vulgaris (rituximab), granuloma faciale (rituximab), perianal Crohn's disease (infliximab), lichen sclerosus (adalimumab), and necrobiosis lipoidica (etanercept and infliximab). Intralesional etanercept reduced pruritus associated with keloids. A case report of the use of infliximab for pyoderma gangrenosum did not demonstrate any efficacy. There was no consistent effect noted with treatments for sarcoidosis (infliximab) or cutaneous lymphoid hyperplasia (rituximab). Local administration of biologic medications may offer an additional method of treating refractory inflammatory dermatoses, but further study is needed to develop standardized dosing protocols, clarify efficacy rates, and identify optimal treatment candidates.